Determination of zinc oxide surge arrester deterioration based of leakage current measurement - 314811 Mohd. Fazley Abu Bakar (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2004